Determination of Technical and Economical Specifications of the Used Tractors at the Market in Tokat Province - Mahmut Selim Yarılan; Gazanfer Ergüneş (Turkish Journal of Agriculture: Food Science and Technology)
In this study, it is aimed to determine the technical and economical specifications of the used tractors put to sale in Tokat province and its districts, such as rated engine power, age, usage hours, tractor structure, maintenance and repair requirements and sale price. Also, it is intended to reveal the tendencies of farmers in tractor demand. The technical and economical specifications of used tractors in the second-hand tractor market in Tokat province and its districts has been analysed. For this purpose, all data has been collected from tractor owners through face-to-face interviews for a total of 408 tractors in 7 districts. According to the data, generally the tractors are standard type, and their age range is between 1 and 58. Based on the data collected from tractor owners, the average annual usage time of the tractors for Tokat is 268 hours, and the average rated power is 58.5 HP (43.6 kW). The remarkable sale reasons of used tractors are model obsolescence, insufficient capacity and need for cash respectively. In the second-hand tractor market, the age of the tractors, rated engine power, brand, usage hours and other technical specifications are primarily factors about pricing. Although 41% of the tractors in the sale have almost completed their lifespan, it has been determined that they can be preferred to some extent. It has been also revealed that tractors with very good service network and tractors that tractor owners can find buyers with the price that they want to sale are most common tractor types in the market. In addition, it is thought that the farmers’ awareness should be developed because they tend to make unconscious buying and selling decisions.